Revenue, access, and engagement via the in-house curated Spotify playlist in Australia. (2nd January 2020) - Morgan, Benjamin A.
ABSTRACT: This article analyzes the perception of recording industry change in Australia through a focus on the curated playlist as a sociotechnical intermediary. During the rapid expansion of commercial music streaming services between 2016 and 2018, musician and recording industry enthusiasm for revenue growth was tempered by trepidation surrounding change. This article presents findings from interview research conducted with Australian artists and music industry professionals to provide insight on the promotion of popular music within the often opaque blend of human and algorithmic structures inside the digital music streaming commodity. It explores the apprehension and enthusiasm over the affordances of the new recommendation and discovery ecosystems, centered around the in-house curated Spotify playlist. Debates surrounding the topics of revenue, access, and engagement are explored. Analysis will demonstrate the increasingly influential role music streaming services and recommendation tools are perceived to play in the sectors of retail, promotion, and distribution.